STRATEGI MARKETING PUBLIC RELATIONS DALAM REBRANDING HSBC INDONESIA UNTUK MEMBENTUK BRAND AWARENESS - Prasetya Yoga Santoso; Rialdo Rezeky M. L. Toruan (Universitas Prof. Dr. Moestopo (Beragama), 2018)
Changing in HSBC brand to HSBC Indonesia to make HSBC management must convey to the people of Indonesia about it. This HSBC rebranding process uses various media and communication activities. The purpose of this research is to know how the process of rebranding HSBC to HSBC Indonesia. The theory used is a model of corporate communication, rebranding, and special events. The research method used qualitative approach. Research method in this research is case study. Data collection techniques include in-depth interviews, direct observation and documentation review. The result of the research shows that the change made by HSBC management to HSBC Indonesia is by integrating with Bank Ekonomi. The change of HSBC to HSBC Indonesia does not use merge terms with Bank Ekonomi but more integration is the merging of the two banks to become one service under HSBC Indonesia. This rebranding process by utilizing various mass media to broadcast various news of HSBC Indonesia. With special events that roadshow 5 big cities Jakarta, Medan, Surabaya, Bandung, and Makassar.